Malformed frogs : the collapse of aquatic ecosystems - Lannoo, Michael J. (University of California Press, 2008)
The widespread appearance of frogs with deformed bodies has generated much press coverage over the past decade. Frogs with extra limbs or digits, missing limbs or digits, or misaligned appendages raise an alarming question: "Are deformed humans next?" Taking a fresh look at this disturbing environmental problem, this reference provides a balanced overview of the science behind the malformed frog phenomenon. Bringing together data from ecology, parasitology, and other disciplines, Michael Lannoo considers the possible causes of these deformities, tells which frogs have been affected, and addres.